High plasma homocysteine and insulin resistance in patients with polycystic ovarian syndrome - Tayebe Hemati; Nasrin Moghadami-Tabrizi; Fateme Davari-Tanha; Bahram Salmanian; Pouya Javadian (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Polycystic ovarian syndrome (PCOS) is a common disease among women in fertility ages and cause severe insulin resistance. Hyperhomocysteinaemia is said to be among the features of PCOS that could influence its outcome.Objective: This study aimed to investigate whether hyperhomocysteinaemia exists in PCOS and if it is related to insulin resistance in the affected patients.Materials and Methods: This prospective study was carried out in a university based fertility clinic. Sixty four PCOS patients and 50 normo ovulatory controls were reviewed for fasting glucose, insulin, homocysteine, luteinizing hormone (LH), and follicle-stimulating hormone (FSH) plasma levels in the blood sample of the 3rd day of their menstrual cycle. Insulin resistance was determined with the fasting glucose (mmol/L) to insulin (mIU/L) ratio and HOMA-IR (Homeostasis model assessment-Insulin resistance). Independent-samples T-test and linear regression test were utilized to analyze the obtained data.Results: Homocysteine levels compared between PCOS patients and control group showed a significant difference. PCOS group was divided into insulin resistant (IR) (LogHOMA-IR≥0.57) and non insulin resistant (NIR) patients. The IR group had significantly higher homocysteine (p-value=0.02), fasting insulin and glucose levels (p-value<0.001) rather than NIR group.Conclusion: PCOS patients have a leaning toward hyperhomocysteinaemia and insulin resistance. Insulin resistant patients are found to have higher homocysteine level